REKONTEKSTUALISASI HUKUM PERNKAHAN BEDA AGAMA DAN STATUS ANAKNYA DI INDONESIA - Juhari, Andi Rezal; Asni; Kurniati (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
This articel discusses how the law and status of marriage differs from religion to child according to Islamic law and positive law in Indonesia. Beginning with a lot of polemics about the marriage of different religions and the status of her children. Especially when the government closed the gap through a Constitutional Court ruling and prohibited judges from accepting applications for registration of non-religious marriages. Then it is necessary to reconstruct the law in order to harmonize the Islamic law with the positive law as a solution to the problem. This type of research is empirical normative research with a juridical, normative and sociological approach. Technical data collection through literary studies and interviews with contemporary South Sulawesi scholars. The analysis technique used is qualitative analysis. The results of the study show that marriages between different religions are legally prohibited, while in Islamic law, contemporary scholars have a khilafist status. So, the form of recontextualization is; 1). The law of different religious marriages today in Indonesia should be permitted with a record in emergency, and marriage that has continued can still be cancelled but must take into account the condition of the child; 2). The marriage status of a child of a different religion can only be passed on to a parent of a new religion, except for a child from a marriage of different religion is permitted; 3. The rights of children from marriages of different religions must be fulfilled by the State and the people around them as well as children in general. The implication of this study is that the government should make changes to the Compilation of Islamic Laws which contains the provisions of marriage of different religions strengthened with the PERMA that contains guidelines for judges to approve marriages of different faiths of an emergency nature. As well as revoking SEMA No. 2 of 2023 for indicating discriminatory occurrences in society.